The Impact of Implementing Android-Based Riyadhah Learning Strategies on the Religious Practices of Students at Masjid Modern Kurir Langit in Barru Regency - A. Arifay Yusuf; Hamdanah; Usman; Kaharuddin; Ahdar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The objective of this research is to assess the extent to which Riyadhah learning influences behavioral and spiritual changes in the daily lives of young Muslims, known as SPA (Santri Pemegang Amanah), within the Masjid Modern Kurir Langit community. This research employs a descriptive qualitative methodology with a phenomenological approach. Data sources include primary and secondary materials. Data collection methods encompass observation, interviews, and documentation. The findings of the study are as follows: (1) The implementation of Riyadhah learning strategies involves equipping SPA with two forms of Islamic education: knowledge (tarbiyah ilmu) and practice (tarbiyah amal). (2) Android-based Riyadhah learning utilizes Android applications as learning media for online education through Zoom Meetings, communication via WhatsApp, and for reporting, attendance, and evaluation using the Time Attendance System application. (3) The impact of Riyadhah learning is to foster correct understanding in accordance with the consensus of scholars (jumhur ulama) aligned with the Ahlus Sunnah wal Jamaah creed (Aqidah Asy’ariyah), following the guidance of the Quran and Sunnah, and to consistently practice Islamic teachings (istiqamah). (4) Factors influencing the implementation of Android-Based Riyadhah Learning Strategies include: inhibiting factors such as lack of awareness and motivation, limited access to technology, limited internet resources, and low interest in digital learning; and supporting factors such as ease of access to information and communication, streamlined attendance tracking, and access to learning applications. The implications of this study are twofold. First, future researchers can further develop studies on the implementation of Riyadhah learning strategies for young Muslims. Second, the Riyadhah learning strategy can be implemented in mosques and hijra communities, although further development and socialization of the strategy are necessary.